Pemikiran Ekonomi Karl Marx Menurut Konsep Ekonomi Islam - Agustin Tampubolon; Bonaraja Purba (Pusat Riset dan Inovasi Nasional, 2024)
Islam and Karl Max are an interesting topic in Indonesia. Apart from the majority of Indonesia's population being Muslim, there are also gaps and gaps in the economic sector. The aim of this article is to re-present the line of thought regarding the relationship between Islam and Karl Marx so that it can be viewed in a more balanced manner. This research methodology is descriptive and qualitative with a historical approach. Research shows that Islam has very different foundations from Marx's ideas, but both aim to create a social order that is just and free from class oppression. However, Islam still recognizes the different potential that exists in every human being. On the other hand, in Marx's view, the difference between people in countries that accumulate money lies in their control of the factors of production.